2019
DOI: 10.3390/biom9020075
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone in Males as Enhanced by Onion (Allium Cepa L.)

Abstract: Testosterone (17β-Hydroxyandrost-4-en-3-one) is the main sex hormone in males. Maintaining and enhancing testosterone level in men is an incessant target for many researchers. Examples of such research approaches is to utilize specific types of food or dietary supplements as a safe and easily reached means. Here, specifically, since 1967 until now, many research studies have revealed the effect of onion on testosterone; however, this link has yet to be collectively reviewed or summarized. To accomplish this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…Moreover, numerous flavonoids and isoflavonoid molecules have also been reported to have steroidogenic effects on Leydig cell lines or animal-based models [ 10 , 14 ]. In addition, ginger, onion, and honey have been demonstrated to have a testosterone-elevating effect in animal-based studies [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, numerous flavonoids and isoflavonoid molecules have also been reported to have steroidogenic effects on Leydig cell lines or animal-based models [ 10 , 14 ]. In addition, ginger, onion, and honey have been demonstrated to have a testosterone-elevating effect in animal-based studies [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference seen may be due to the effect of the difference in active principle and antioxidant composition (Slimestad et al, 2007) of the specie of the Allium. Banihani (2019) documented that Allium cepa L. extract enhances testosterone production in males and the mechanisms is mainly by enhancing LH production, neutralizing the damaging effects of formed free radicals and enhancing the antioxidant defence mechanism in the testis, ameliorating insulin resistance, promoting nitric oxide production in Leydig cells, and altering the activity of 5' AMPactivated protein kinase. The administered Allium cepa L. scaly leaf extract in this present study significantly increased LH and FSH but not testosterone levels and this might be due to interference with LH receptors within Leydig cells and hence the non-significance change in testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…[ Banihani reported that onion or its extracts (e.g., aqueous extract ~30 mg day −1 ) enhances testosterone production in males. The mechanisms by which onion enhances testosterone production in males is mainly by enhancing the production of luteinizing hormone, neutralizing the damaging effects of the formed free radicals, mainly in the testes, enhancing the antioxidant defense mechanism in the testis, ameliorating insulin resistance, promoting nitric oxide production in Leydig cells, and altering the activity of 5′ AMPactivated protein kinase [17]. [4] Chauhan et al reported that ethanolic extract of seeds of A. longifolia were administered to groups of rats in 100, 150 and 200 mg kg⁻¹ doses which exhibited pronounced anabolic effects in treated animals, as evidenced by gains in the body and reproductive organ weights.…”
Section: Therapeutic Uses [3]mentioning
confidence: 99%